Mechanisms of Photosensitized Lipid Oxidation and Membrane Permeabilization - Bacellar, Isabel O. L. (ACS Omega, 2019)
[Image: see text] Lipid oxidation encompasses chemical transformations affecting animals and plants in many ways, and light is one of the most common triggers of lipid oxidation in our habitat. Still, the molecular mechanisms and biological consequences of photoinduced lipid oxidation were only recently understood at the molecular level. In this review, we focus on the main mechanisms of photosensitized lipid oxidation and membrane permeabilization, dissecting the consequences of both singlet oxygen and contact-dependent pathways and discussing how these reactions contribute to chemical and biophysical changes in lipid membranes. We aim to enable scientists to develop novel and more efficient photosensitizers in photomedicine, as well as better strategies for sun protection.